Association Between Diabetic Neuropathy and Fall Risk in Patients with Type 2 Diabetes Mellitus at Siti Khodijah Hospital Sepanjang - Mochamad Reza Irmansyah; Nurma Yuliyanasari; Laily Irfana; Bagus Aulia Mahdi (Universitas Muhammadiyah Surabaya, 2026)
Diabetic neuropathy has been recognized as a prevalent complication of type 2 diabetes mellitus, correlated with diminished balance function and an elevated likelihood of falls, which may be associated with substantial morbidity and reduced quality of life. The present study was undertaken to investigate the association between diabetic neuropathy and fall risk in patients with type 2 diabetes mellitus at Siti Khodijah Hospital, Sepanjang, using a cross-sectional design among 56 patients selected through purposive sampling. Diabetic neuropathy status was ascertained from medical record documentation reflecting clinical diagnoses established by internal medicine and neurology specialists, whereas fall risk was evaluated by administering the Timed Up and Go (TUG) test. Of participants with diabetic neuropathy, 26 of 35 patients (74.3%) were identified as higher fall risk, compared to 8 of 21 patients (38.1%) without diabetic neuropathy. Chi-square analysis yielded a statistically significant association between diabetic neuropathy and TUG-based fall risk classification (p = 0.007, r = 0.338), with an odds ratio of 4.694 (95% CI: 1.469–15.005). These results suggest that early detection of diabetic neuropathy and prompt initiation of preventive interventions may be warranted to reduce fall-related outcomes in this population.